Experimental study of temperatures during drilling of ex-vivo bovine bones - Fernandes, M.G.A. (2016)
he thermal bone necrosis induced during a drilling process is a frequent and potential phenomenon, which contributes to post-operative problems. The frictional heat generated from the contact between the drill bit and the hole wall is unavoidable. However, understanding advanced techniques for acquiring reliable thermal data on bone drilling is important to ensure the quality of the drilled hole.